The Lomfjorden Fault Zone in eastern Spitsbergen (Svalbard) - Piepjohn, Karsten; Dallmann, Winfried; Elvevold, Synnøve (The Geological Society of America, 2019)
The Lomfjorden Fault Zone in the eastern part of Spitsbergen is one of the prominent structures in Svalbard oriented parallel to the continental margin of the Barents Shelf. It consists of a network of three N–S-striking major faults (Veteranen, Lomfjorden, and Agardhbukta faults), two N–S-striking reverse faults (Lomfjella and Bjørnfjellet reverse faults), and a number of NE–SW- and NNW–SSE-striking normal, reverse, and strike-slip faults. Structural data collected during fieldwork in the northern and central segments of the fault zone, in combination with published data from the southernmost segment, indicate that N–S-striking reverse faults in the Lomfjorden Fault Zone were caused by convergence transferred from the West Spitsbergen Fold-and-Thrust Belt eastward along detachments during an initial phase of the Eurekan deformation in the early Eocene. The W–E contraction was followed by sinistral and dextral strike-slip tectonics along the Lomfjorden Fault Zone during a later phase of the Eurekan deformation in the late Eocene. The NNW–SSE-striking reverse and normal faults are oriented obliquely between the N–S-striking, en-échelon Lomfjorden and Agardhbukta faults. Shortening and extension across these, respectively, can be explained by left-stepping contractional overstep or left-stepping wrench faults in an overall dextral and left-stepping extensional overstep or left-stepping wrench faults in an overall sinistral, N–S-trending strike-slip system. It was not possible to determine if the sinistral phase pre-dated the dextral one or vice versa. The presence of a large granite massif, the Newtontoppen Granite, is suspected to influence or even control the course of the faults and their transfer systems. The involvement and reactivation of preexisting Carboniferous and even older structures and the superimposition of convergent and lateral movements along the Lomfjorden Fault Zone is similar to large fault zones in North Greenland and on Ellesmere Island, indicating that it represents an important element of ...